Peran Guru Dalam Membina Karakter Religius Peserta Didik Di RA Al-Hidayah: THE ROLE TEACHER TO DEVELOPING RELIGIOUS CHARACTER OF STUDENTS AT RA AL-HIDAYAH - SITI MA RIFATUL MUNAWAROH; ASTUTI DARMIYANTI; NIDA’UL MUNAFIAH (incrementapedia, 2023)
The job of a teacher is more than just teaching the material in class; In addition, he teaches, directs, supports and assists students in cultivating positive attitudes and behaviors to help them become good people. Other experts agree with Uno (2008), supporting Salahudin and Irwanto's argument regarding the importance of the teacher's role as a model for developing religious character: The teacher must be able to be an example for his students because he represents a group of people who can be imitated and admired. Therefore, the role of school counselors in the learning process is indispensable, especially in terms of conveying knowledge and information related to moral values. Character education is required so that students are able to anticipate and respond to future challenges with religious insight. Religious character development can also be assisted by instilling religious values and teaching children to always behave well. PAUD activities enable children to worship, understand and believe in God's creation, love and respect others, and achieve their goals. According to the findings of this study, teachers at RA Al-Hidayah have a role in fostering the religious character of their students because they can always help students in developing good religious character. Religious character education provides the first opportunity for teachers to assist students in realizing their full potential.